2010
DOI: 10.1038/cmi.2010.43
|View full text |Cite
|
Sign up to set email alerts
|

Non-hematopoietic cells contribute to protective tolerance to Aspergillus fumigatus via a TRIF pathway converging on IDO

Abstract: Innate responses combine with adaptive immunity to generate the most effective form of anti-Aspergillus immune resistance. Whereas the pivotal role of dendritic cells in determining the balance between immunopathology and protective immunity to the fungus is well established, we determined that epithelial cells (ECs) also contributes to this balance. Mechanistically, EC-mediated protection occurred through a Toll-like receptor 3/Toll/IL-1 receptor domain-containing adaptor-inducing interferon (TLR3/TRIF)-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 48 publications
4
73
1
Order By: Relevance
“…Activation of IDO via the TLR3/ TRIF pathway confers tolerogenic and Th1-activating potential to lung DCs in murine aspergillosis. 18,19 Consistently, the enzyme was not induced in infection in the lung of Tlr3 Ϫ/Ϫ mice despite being expressed at the basal level (supplemental Figure 5). Therefore, through IDO, TLR3 likely contributes to the promotion of protective tolerance to the fungus in infection and to the down-regulation of Th17 responses, as shown previously with other lung infections.…”
Section: Cd8 ؉ T Cells Do Not Expand In Tlr3 ؊/؊ Mice After Infectionmentioning
confidence: 54%
See 1 more Smart Citation
“…Activation of IDO via the TLR3/ TRIF pathway confers tolerogenic and Th1-activating potential to lung DCs in murine aspergillosis. 18,19 Consistently, the enzyme was not induced in infection in the lung of Tlr3 Ϫ/Ϫ mice despite being expressed at the basal level (supplemental Figure 5). Therefore, through IDO, TLR3 likely contributes to the promotion of protective tolerance to the fungus in infection and to the down-regulation of Th17 responses, as shown previously with other lung infections.…”
Section: Cd8 ؉ T Cells Do Not Expand In Tlr3 ؊/؊ Mice After Infectionmentioning
confidence: 54%
“…Immunoblotting for IDO was performed with rabbit polyclonal IDO-specific Ab on total lung cells. 18 Scanning densitometry was For personal use only. on May 12, 2018. by guest www.bloodjournal.org From done on a Scion Image apparatus.…”
Section: Western Blottingmentioning
confidence: 99%
“…Sustained IDO induction depends on noncanonical NF-kB activation (19). Because TRIF-mediated signaling may involve noncanonical NF-kB family members (38,39), we hypothesized that a TLR7/TRIF axis could be at work in IDO induction by GpC-ODN. Our data revealed that GpC-ODN acts as a tolerogenic signal for pDCs, which are also capable of initiating IDOdependent long-term suppression independent of IDO's catalytic function (40).…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6, BALB/c, and Md2 2/2 recipient mice were exposed to a lethal dose of 9 Gy, infused i.v. with T cell-depleted donor cells ($10 3 10 6 ), and infected with Aspergillus conidia a week later (29).…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Dendritic cells (DC), macrophages, and epithelial cells were purified from lungs as described (25,29). Murine CD11b + Gr-1 + PMN were positively selected with magnetic beads (Miltenyi Biotec) from the peritoneal cavity of uninfected WT 8 h after the i.p.…”
Section: Cellsmentioning
confidence: 99%